2021
DOI: 10.1093/ve/veab054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics and evolutionary analysis of a highly recombinant begomovirus, Cotton leaf curl Multan virus, and associated satellites

Abstract: Cotton leaf curl Multan virus (CLCuMuV) and its associated satellites are a major part of the cotton leaf curl disease (CLCuD) caused by the begomovirus species complex. Despite the implementation of potential disease management strategies, the incessant resurgence of resistance-breaking variants of CLCuMuV imposes a continuous threat to cotton production. Here, we present a focused effort to map the geographical prevalence, genomic diversity and molecular evolutionary endpoints that enhance disease complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…Mixed infections and high viral replication levels are two conditions that may promote recombination [103]. As recombination hotspots, the IR, V1, V2, and C1 regions of the genome have been identified [112][113][114][115][116][117][118]. Studies from the Punjab regions of Pakistan and India recently suggest that CLCuMuV has reemerged in the Indian subcontinent, which is consistent with observations from earlier studies.…”
Section: Recombination and Evolutionsupporting
confidence: 63%
“…Mixed infections and high viral replication levels are two conditions that may promote recombination [103]. As recombination hotspots, the IR, V1, V2, and C1 regions of the genome have been identified [112][113][114][115][116][117][118]. Studies from the Punjab regions of Pakistan and India recently suggest that CLCuMuV has reemerged in the Indian subcontinent, which is consistent with observations from earlier studies.…”
Section: Recombination and Evolutionsupporting
confidence: 63%
“…Attributing them to the small genome size with a high potential for genomic variation (due to mutation and recombination), BGVs are attractive models for studying the evolutionary and ecological factors driving their emergence [47]. Substitution rates (or µ) of whitefly vectored BGVs have been described to be equally high as those of ssRNA viruses [48,49], and positive selection pressure on mutations or the products of recombination events plays a crucial role in BGV evolutionary dynamics [50,51]. Regulatory mechanisms of BGVs and RNA viruses promote host adaptation; the betasatellite silencing suppressor βC1 avoids excessive inhibition of antiviral pathways and cell toxicity through autophagy activation [52]; Cucumber mosaic virus (CMV) silencing suppressor 2b and its interacting partner ARGONAUTE 1 (AGO1) is antagonized by the viral CP and 1a [53,54]; and the regulated proteolysis of the Plum pox virus (PPV) P1 modulates the HCPro silencing suppressor activity to promote the long-term virus fitness [55].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the role of whitefly Vg in the transovarial transmission of TYLCV has been linked with evolution and global spread of begomoviruses (Wei et al, 2017). Recently, it was found that a midgut-synthesized Vg plays functional role during whitefly-mediated transmission by TYLCV by facilitating the movement of virions across the midgut barriers of whitefly vector (He et al, 2021). Despite the well-known role of insect Vgs in the virus transmission, it is yet unknown how CLCuMuV manipulate this receptor protein to attain differential transmission by whitefly cryptic species.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the virus has rapidly spread to major cotton-growing countries, particularly in South Asia. A recent study highlights the geographical distribution and standing genetic diversity of highly recombinant and rapidly evolving CLCuMuV populations across major cotton-producing countries ( Farooq et al, 2021 ). Although local transmission of CLCuMuV is attributed to the whitefly cryptic species complex, the source of virus spread from Pakistan to China or other countries has not been well-established ( Ashfaq et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%